Dialogue Leading to A Problematic Situation and Its Place In School Education - Akhmedov B.A. (Zien Journals, 2024)
the article talks about the methodology of approach to problem-based education, its skills and principles.
Keywords: education; pedagogy; educational efficiency; educational technology